The Freiburg Visual Acuity test--automatic measurement of visual acuity - Bach, M (Optometry and vision science, 1996)
The Freiburg Visual Acuity test is an automated procedure for self-administered measurement of visual acuity. Landolt-Cs are presented on a monitor in one of eight orientations. The subject presses one of eight buttons, which are spatially arranged on a response box according to the eight possible positions of the Landolt-Cs' gap. To estimate the acuity threshold, a best PEST (best Parameter Estimation by Sequential Testing) procedure is used in which a psychometric function having a constant slope on a logarithmic acuity scale is assumed. Measurement terminates after a fixed number of trials. With computer monitors, pixel-discreteness artifacts limit the presentation of small stimuli. By using anti-aliasing, i.e., smoothing of contours by multiple gray levels, the spatial resolution was improved by a factor of four. Thus, even the shape of small Landolt-Cs with oblique gaps is adequate and visual acuities from 5/80 (0.06) up to 5/1.4 (3.6) can be tested at a distance of 5 m.